Best Practices in American Indian Student Retention at East Carolina University in Juxtaposition to the University of North Carolina System - Griffin, Joshua (My University, 2015)
At just 0.9% of the total undergraduate student population, American Indian (i.e. Native American, Alaska Native1) students are underrepresented at most of the universities in the University of North Carolina (UNC) system (Headcount). A search of the UNC system demonstrated that university resources allocated for this population of students are provided in a number of different ways without much cohesion across the system. Some of these resources are common across many universities while others are university-specific. Collectively, these resources have the potential to increase the enrollment, retention, and graduation of American Indian students with a wide-ranging assortment of initiatives and programs, from recruitment to culturally-based events, but these have not previously been consolidated for consideration by students, universities, or the UNC system for use. This thesis introduces these different resources and identifies the strengths and limitations of the resources that are useful for increasing the enrollment, retention, and graduation of American Indian students at East Carolina University. Frequent criticisms of higher education regarding American Indian student retention and graduation point to the absence of American Indian university faculty, programs supporting cultural and contemporary needs of American Indian students, and funding for American Indian students to overcome economic barriers. The primary sources for American Indian students to receive support from the UNC system are provided through academic opportunities, personal relationships, and cultural programs.
Keywords: American Indian recruitment retention graduation